2019
DOI: 10.1371/journal.pone.0223164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pimobendan on physical fitness, lactate and echocardiographic parameters in dogs with preclinical mitral valve disease without cardiomegaly

Abstract: Pimobendan has gained enormous importance in the treatment of mitral valve disease in dogs. The current consensus statement of the American College of Veterinary Internal Medicine (ACVIM) recommends a treatment for dogs with symptomatic disease and dogs with asymptomatic disease with radiographic and echocardiographic signs of cardiomegaly. To investigate whether these dogs also benefit from a therapy with pimobendan, 21 dogs with mitral valve disease ACVIM B1 underwent a standardized submaximal exercise test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…These findings might indicate a positive effect of pimobendan treatment in some dogs at stage ACVIM B1. As in previous studies, no major adverse effects could be detected in the pimobendan treatment group [ 8 , 9 , 31 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings might indicate a positive effect of pimobendan treatment in some dogs at stage ACVIM B1. As in previous studies, no major adverse effects could be detected in the pimobendan treatment group [ 8 , 9 , 31 ].…”
Section: Discussionsupporting
confidence: 78%
“…All dogs included in the study underwent an SSET on a motorised treadmill (“quasar”, h/p/cosmos sports and medical GmbH, Nussdorf-Traunstein, Germany) as recently established by Wall et al and utilised in the predecessor study by Iwanuk et al [ 8 , 9 , 19 ]. Before starting the examinations for the study, dogs had been accustomed to the treadmill and the speed of the treadmill had been slowly increased to their respective comfort speed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A standardised, submaximal exercise test on a treadmill has already been developed and tested in dogs with early mitral valve disease [ 33 ], and has been used to investigate the effect of medication in these patients [ 34 , 35 ]. These studies, and others, showed that it is possible to acclimatise untrained dogs to a treadmill [ 33 , 34 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dogs have been classified into stages A, B, C, and D ( 4 , 5 ). High blood lactate concentrations are frequently observed in dogs with abnormal thoracic radiographs such as cardiomegaly and pulmonary parenchyma ( 6 ). Dogs with degenerative mitral valve disease often have impaired renal function.…”
Section: Introductionmentioning
confidence: 99%